The First World War Diaries of the Rt. Rev. Llewellyn Gwynne, July 1915-July 1916. - Howson, Peter (Peter James) (Boydell & Brewer, Incorporated, 2019)
The Right Reverend Llewellyn Gwynne's diaries offer a unique insight into a period of change for the army, chaplains and the Church of England during a critical period of the First World War.
Description based upon print version of record.
Keywords: Gwynne, Llewellyn H., -- 1863-1957 -- Diaries.; Great Britain. -- Army. -- British Expeditionary Force -- Chaplains -- Diaries.; Church of England -- Clergy.; Church of England -- Clergé.; Gwynne, Llewellyn H., -- 1863-1957; Church of England; Great Britain. -- Army. -- British Expeditionary Force; World War, 1914-1918 -- Chaplains -- Great Britain -- Diaries.; Guerre mondiale, 1914-1918 -- Aumôniers -- Grande-Bretagne -- Journaux intimes.; Armed Forces -- Chaplains; Chaplains; Clergy; Great Britain; 1914-1918; Diaries